Signal recovery from partial fractional fourier transform information - Cetin, Ahmet Enis; Özaktaş, Hakan; Özaktaş, Haldun Memduh (My University, 2004)
The fractional Fourier transform has found many applications in signal and image processing and optics. An iterative algorithm for signal recovery from partial fractional Fourier transform information is presented. The signal recovery algorithm is constructed by using the method of projections onto convex sets and convergence of the algorithm is assured.
2004 First International Symposium on Control, Communications and Signal Processing, ISCCSP 2004 --
Keywords: Hermite polynomials; Iterative algorithms; Signal recovery; Algorithms; Computer simulation; Eigenvalues and eigenfunctions; Fourier transforms; Iterative methods; Mathematical operators; Matrix algebra; Polynomials; Signal processing